Quadhelix: a tool for cleft lip and palate patients management. Report of three cases - Lozano Llaury, Lucia (2020)
As cleft lip and palate is one of the most frequent congenital anomalies, orthodontists should know about transverse management in these patients, to ignore it might aggravate the fissure, as the biomechanical effects in these patients require special care due to their maxillary structure. This case series include three patients, one with a sequel of right unilateral cleft lip and palate, one bilateral and the last one with left unilateral cleft lip and palate. The maxillary transverse constriction and the discrepancy with the mandibular width, led to choice quadhelix appliance to solve this problem. In all three cases the transversal treatment objectives were achieved. In conclusion the quadhelix appliance is a reliable alternative which has advantages such as a slow expansion producing less tissue resistance around the circummaxillary structures and improves bone formation in the intermaxillary suture; similarly, it has greater dentoalveolar effects that does not cause buccal cortical bone loss; additionally, it shows better muscular adaptation and low chance of relapse.